Diet and density effects on growth, proximate composition and fatty-acid profile of Hediste diversicolor juveniles - Zabihollah Pajand; Ayoub Yousefi; Hamed Abdollahpour; Esmaeil Hosseinnia; Arash Lebria; Younes Golalipour; Parham Pajand; Naghmeh Jafari Pastaki; Mohebali Pourgholam (PLoS ONE, 2026)
This study evaluated the nutritional quality of Hediste diversicolor cultivated using waste from beluga sturgeon ( Huso huso ) aquaculture. Over a 60-day trial, polychaetes were reared at four stocking densities (1000–7500 individuals per square meter (ind./m²)) and fed either commercial sturgeon feed or processed farming waste. Results demonstrated that sturgeon waste effectively supported polychaete culture, with survival rates ranging from 53% to 80%. However, worms fed commercial feed exhibited superior growth, yielding over three times greater biomass than waste-fed groups. Nutritional composition was significantly affected by both diet and density. Worms fed commercial feed at an intermediate density (2500 ind./m²) achieved the highest protein content (9.23%) and most beneficial fatty acid profile, characterized by a high PUFA content (46.85%) and n-3/n-6 ratio (0.39). While waste-fed worms showed reduced nutritional quality, an intermediate density of 2500 ind./m² also optimized their composition. A comparative analysis confirmed the commercial feed was richer in protein and essential fatty acids (EPA + DHA) than the processed waste. The study confirms the viability of using sturgeon waste to produce polychaete biomass for aquaculture. However, nutritional trade-offs suggest supplemental feeding may be required to achieve premium quality for aquaculture feed, providing critical benchmarks for implementing circular economy principles in aquaculture systems.